Marriage agreement in a positive legal perspective on inheritance division - Rizka Syafriana (Indonesian Journal Education, 2026)
This study examines the legal position and implications of marriage agreements in the division of inheritance within the Indonesian legal system. A marriage agreement, as regulated in the Civil Code and Law Number 1 of 1974 concerning Marriage, provides autonomy for spouses to arrange the separation of property based on the principle of freedom of contract, while still adhering to legal requirements and public order. Using a normative juridical approach, this research analyzes relevant laws, legal doctrines, and scholarly literature to understand the impact of such agreements. The findings reveal that marriage agreements have both internal implications between spouses and external implications involving third parties, particularly in matters of debt liability and inheritance distribution. Despite offering legal certainty, the application of marriage agreements remains limited by juridical constraints to ensure fairness and balance. The study highlights the need for regulatory reform to better accommodate evolving social dynamics and recognize both monetary and non-monetary contributions in household life, thereby promoting substantive justice in inheritance division.